Strategi Promosi Objek Wisata oleh Dinas Kebudayaan dan Pariwisata Kota Tanjungpinang - SURYANTI NENGSIH, NENG; Mukhlis, Suhardi; Usman siam, Nurbaiti; Junriana, Junriana; Yulianto putri, Tania (STISIPOL Raja Haji, 2022)
Tanjungpinang City is rich in tourism potential, in the form of natural/historical and cultural tourism. This opens up investment opportunities in the tourism sector on offer. However, the problem is that the implementation of the promotion strategy carried out by the Tanjungpinang City government, namely the Tanjungpinang City Culture and Tourism Office has not been maximized. The purpose of this study was to determine the Tourism Object Promotion Strategy of Tanjungpinang City by the Department of Culture and Tourism of Tanjungpinang City. This research is descriptive qualitative approach. Research Locations at the Department of Culture and Tourism of Tanjungpinang City Sources and types of data are primary data and secondary data. Technique data collection through interviews and observations. This research is based on the theory of Fred R. David (2011) “which describes that the strategic management process consists of three stages, namely, formulating strategies, implementing strategies and evaluating strategies. From the results of the analysis carried out, it can be concluded that the Strategy of the Tanjungpinang City Culture and Tourism Office in developing and promoting tourism objects in the Tanjungpinang city by carrying out several forms of promotion, namely events marketing and cooperation between Pokdarwis in all urban villages of Tanjungpinang city. The suggestion that the author can give in this case to the Tanjungpinang City Culture and Tourism Office is optimizing the use of online media in tourism object promotion activities to be one of the major impact alternatives for promotional activities carried out by the Tanjungpinang City Tourism and Culture Office and the Guidance of Arts and Culture Groups, Human Resource Development of Cultural Actors.